Comparison of Stage and Lymph Node Ratio in Young and Older Patients with Colorectal Cancer Operated in a Tertiary Hospital in Nepal - Ghimire, Bikal; Singh, Yogendra Prasad; Kurlberg, Goran; Wettergren, Yvonne (Journal of Nepal Health Research Council, 2018)
Background: Colorectal cancer is being diagnosed more frequently in the young and it presents in an advanced stage. In TNM staging, stage depends on tumor size and number of positive nodes, which depend on location of tumor as well as the extent of dissection.The lymph node ratio is regarded as a more reliable marker for prognosis. In this study, we compare epidemiology of colorectal cancer in the young ( 40 years) and clinic-pathological data such as site of lesion, clinical stage, and lymph node ratio were compared.Results: Of the 95 patients of colorectal cancer, 25 patients were of age ≤ 40 years (26%) and they had a higher median stage at diagnosis. In patients above 40 years, it was diagnosed at a relatively earlier stage. The mean number of positive nodes was 11.64 in younger patients whereas it was 18.34in those more than 40 years of age,but younger patients had higher lymph node ratio than elderly (0.31 vs 0.13) (P-value ≤ 0.005).Conclusions: Young patients with colorectal cancer tend to have more advanced disease. The lymph node metastasis and lymph node ratio tend to be higher in young patients.